Anti-proliferative effect of methanolic extract of Gracilaria tenuistipitata on oral cancer cells involves apoptosis, DNA damage, and oxidative stress - Yeh Chi-Chen; Yang Jing-Iong; Lee Jin-Ching; Tseng Chao-Neng; Chan Ya-Ching; Hseu You-Cheng; Tang Jen-Yang; Chuang Li-Yeh; Huang Hurng-Wern; Chang Fang-Rong; Chang Hsueh-Wei (BMC, 2012)
Abstract Background Methanolic extracts of Gracilaria tenuistipitata (MEGT) were obtained from the edible red algae. Previously, we found that water extract of G. tenuistipitata was able to modulate oxidative stress-induced DNA damage and its related cellular responses. Methods In this study, the methanol extraction product MEGT was used to evaluate the cell growth inhibition in oral cancer cells and its possible mechanism was investigated. Results The cell viability of MEGT treated Ca9-22 oral cancer cell line was significantly decreased in a dose-response manner (p < 0.05). The sub-G1 population and annexin V intensity of MEGT-treated Ca9-22 cancer cells were significantly increased in a dose-response manner (p < 0.0005 and p < 0.001, respectively). The γH2AX intensities of MEGT-treated Ca9-22 cancer cells were significantly increased in a dose-response manner (p < 0.05). The reactive oxygen species (ROS) and glutathione (GSH)-positive intensities of MEGT-treated Ca9-22 oral cancer cells were significantly increased and decreased, respectively, in a dose-response manner (p < 0.05). The DiOC2(3) intensity for mitochondrial membrane potential (MMP) of MEGT-treated Ca9-22 cancer cells was significantly decreased in a dose-response manner (p < 0.05). Conclusions These results indicated that MEGT had apoptosis-based cytotoxicity against oral cancer cells through the DNA damage, ROS induction, and mitochondrial depolarization. Therefore, MEGT derived from the edible algae may have potential therapeutic effects against oral squamous cell carcinoma (OSCC).